Mycobacterium tuberculosis Zinc Metalloprotease-1 Assists Mycobacterial Dissemination in Zebrafish - Vemula, Mani H.; Medisetti, Raghavender; Ganji, Rakesh; Jakkala, Kiran; Sankati, Swetha; Chatti, Kiranam; Banerjee, Sharmistha (Frontiers in Microbiology, 2016)
Zinc metalloprotease-1 (Zmp1) from Mycobacterium tuberculosis (M.tb), the tuberculosis (TB) causing bacillus, is a virulence factor involved in inflammasome inactivation and phagosome maturation arrest. We earlier reported that Zmp1 was secreted under granuloma-like stress conditions, induced Th2 cytokine microenvironment and was highly immunogenic in TB patients as evident from high anti-Zmp1 antibody titers in their sera. In this study, we deciphered a new physiological role of Zmp1 in mycobacterial dissemination. Exogenous treatment of THP-1 cells with 500 nM and 1 μM of recombinant Zmp1 (rZmp1) resulted in necrotic cell death. Apart from inducing secretion of necrotic cytokines, TNFα, IL-6, and IL-1β, it also induced the release of chemotactic chemokines, MCP-1, MIP-1β, and IL-8, suggesting its likely function in cell migration and mycobacterial dissemination. This was confirmed by Gap closure and Boyden chamber assays, where Zmp1 treated CHO or THP-1 cells showed 2 fold increased cell migration compared to the untreated cells. Additionally, Zebrafish-M. marinum based host-pathogen model was used to study mycobacterial dissemination in-vivo. Td-Tomato labeled M. marinum (TdM. marinum) when injected with rZmp1 showed increased dissemination to tail region from the site of injection as compared to the untreated control fish in a dose-dependent manner. Summing up these observations along with the earlier reports, we propose that Zmp1, a multi-faceted protein, when released by mycobacteria in granuloma, may lead to necrotic cell damage and release of chemotactic chemokines by surrounding infected macrophages, attracting new immune cells, which in turn may lead to fresh cellular infections, thus assisting mycobacterial dissemination.